Enhancing PMO Capabilities through PMO Maturity Level Assessment at PT AtoZ - Firmansyah, Bayu Aditya; Veronika, Alin; Avianto, Ika; Nisrina, Dhia Tsuraya (Journal of Project Management Research, 2025)
This study assesses the Project Management Office (PMO) maturity at PT AtoZ, an Indonesian state-owned enterprise, to identify areas for improvement and enhance its contribution to organizational success within a rapidly changing global market. The increasingly complex and dynamic nature of project management necessitates the adoption of best practices and a robust PMO to ensure effective project delivery and strategic alignment. This research aimed to assess the current PMO capabilities at PT AtoZ, identify areas for improvement, and develop an actionable plan to enhance its effectiveness. Utilizing the PMO Maturity Cube model, a mixed-methods approach evaluated PMO functions across strategic, tactical, and operational dimensions. The findings revealed an overall intermediate level of PMO maturity (47.01%), with significant variations across functional areas. While operational functions demonstrated relatively higher maturity, substantial gaps were identified in strategic functions, particularly in advising senior management (scoring 0/4), and tactical functions such as resource allocation and methodology implementation. Key strengths were observed in stakeholder interaction and project documentation management. In conclusion, while the PMO at PT AtoZ demonstrates some positive aspects, significant improvement is needed, particularly in strategic advisory and tactical project management. A structured action plan, including enhanced training and development, process standardization, and strengthened resource allocation mechanisms, is recommended. This research contributes valuable insights into PMO maturity assessment and improvement within a large, complex organization, highlighting the importance of aligning PMO capabilities with broader organizational strategic objectives. Further research should explore the long-term impact of implementing the proposed recommendations.